PENGARUH INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Wardah Toko Lova Kota Bengkulu) - Reni Indriani; Desi Fitria; Fatihatunnisa (Universitas Muhammadiyah Bengkulu, 2023)
This study aims to determine the effect of product innovation and product quality on purchasing decisions (a study on consumers at Wardah Toko Lova, Bengkulu City). This research was conducted on consumers of Wardah Toko Lova Bengkulu City, the population used in this study were all consumers who bought Wardah Toko Lova Bengkulu City. Samples used was 150 respondents. The results study indicate that partially the product innovation variable has a significant effect on the purchasing decision variable, H1 is accepted and product quality has a significant effect on the purchasing decision variable, H2 is accepted. While the f test of product innovation (X1) and product quality (X2) has a significant influence on Wardah's Purchase Decision (Y) at the Lova Store, Bengkulu City. So that H3 is accepted. The overall significant level is (sig = 0.000 <0.050). As well as having a regression equation Y = 4.060 + 0.233X1 + 0.224X2. And the coefficient of determination (R2) for the value of R Square is 0.478. The most dominant factor with the largest regression coefficient value is the product innovation variable (X1) with a value of 0.233.